Moodle-integrated flipped classroom design to enhance students' mathematical conceptual understanding - Fitry Wahyuni; Izwita Dewi; Faiz Ahyaningsih (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2026)
Mathematical conceptual understanding is an essential ability that enables students to interpret, connect, represent, and apply mathematical ideas. However, students still experience difficulties in developing this ability, partly due to procedural and teacher-centered learning practices. This study aimed to design and develop a Moodle-integrated Flipped Classroom and evaluate its validity, practicality, and effectiveness in enhancing students’ mathematical conceptual understanding on geometric transformation material. This study employed a Research and Development approach using the Plomp model, consisting of preliminary research, prototyping, and assessment phases. The participants were 32 eighth-grade students at one state junior high school in Medan, North Sumatra. Data were collected through expert validation sheets, teacher and student practicality questionnaires, Moodle log activity data, and pre-test and post-test instruments. The results showed that the Moodle-integrated Flipped Classroom was very valid with a score of 90.6%, very practical with a score of 86.3%, and effective based on the predetermined effectiveness criterion, as indicated by a moderate N-Gain score of 0.51. Learning analytics data showed high student engagement, including a 90.6% video completion rate, an 89.6% quiz completion rate, and 288 forum interactions with a 1.8:1 reply-to-post ratio. The highest improvements occurred in connecting mathematical concepts and applying concepts in new situations. These findings indicate that a systematically designed Moodle-integrated Flipped Classroom can support students’ mathematical conceptual understanding through structured independent learning, interactive activities, and collaborative discussion.